2014
DOI: 10.1111/bjh.13256
|View full text |Cite
|
Sign up to set email alerts
|

The molecular spectrum and clinical impact of DIS3 mutations in multiple myeloma

Abstract: SummaryMultiple myeloma (MM) is a plasma cell neoplasm that presents with a major biological and clinical heterogeneity. We here investigated the spectrum of clonal and subclonal mutations of DIS3, an active part of the exosome complex, that may play a role in the development or progression of MM. The whole coding sequence of DIS3 was subjected to deep sequencing in 81 uniformly-treated MM patients and 12 MM cell lines and the overall occurrence of DIS3 mutations as well as the presence of DIS3 mutations in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 56 publications
5
89
5
1
Order By: Relevance
“…Our results raise the possibility that defects in the two different conformations cause different human diseases. Specifically, multiple myeloma genomes often contain mutations in the Rrp44 exonuclease domain, but not in other RNA exosome subunits (Weissbach et al, 2015). In contrast, pontocerebellar hypoplasia is caused by point mutations in the exo-9 core (EXOSC3 and EXOSC8; Boczonadi et al, 2014; Wan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results raise the possibility that defects in the two different conformations cause different human diseases. Specifically, multiple myeloma genomes often contain mutations in the Rrp44 exonuclease domain, but not in other RNA exosome subunits (Weissbach et al, 2015). In contrast, pontocerebellar hypoplasia is caused by point mutations in the exo-9 core (EXOSC3 and EXOSC8; Boczonadi et al, 2014; Wan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These molecular functions are best defined in yeast, but many are conserved in human cells (Staals and Pruijn, 2011). In human patients, different mutations that affect RNA exosome activity are associated with distinct human diseases: multiple myeloma (Weissbach et al, 2015), pontocerebellar hypoplasia (Boczonadi et al, 2014; Wan et al, 2012), trichohepatoenteric syndrome (Fabre et al, 2012; Hartley et al, 2010), and most recently, a distinct disorder that has not yet been named (Di Donato et al, 2016). A thorough investigation of the structure and function of the RNA exosome is essential to understand how the RNA exosome carries out all of these functions, and how RNA exosome defects cause these very diverse diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Human DIS3 attracted our attention because it is essential for the survival of vertebrate cells (Tomecki et al 2014). Interestingly, DIS3 is frequently mutated in multiple myeloma and other cancers (Chapman et al 2011;Walker et al 2012;Weißbach et al 2014). Approximately 10%-15% of multiple myeloma cases have specific hemizygous or homozygous mutations in the DIS3 RNB domain, which leads to DIS3 dysfunction, but not complete inactivation (Tomecki et al 2014).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…While the effects of DIS3 in the context of cancer have not previously been explored in depth, mutations in DIS3 have been observed in several cancer types (15)(16)(17)(18)(19)(20). Perhaps the most striking example is multiple myeloma (MM), which shows a 10-18.5% somatic mutation rate in different studies (15,16,20,21). DIS3 ribonuclease II (RNB) domain mutations observed in MM were shown to be synthetic lethal with catalytic mutations in the PIN domain, suggesting a possible drug target (22).…”
Section: Discussionmentioning
confidence: 99%
“…DIS3 ribonuclease II (RNB) domain mutations observed in MM were shown to be synthetic lethal with catalytic mutations in the PIN domain, suggesting a possible drug target (22). Furthermore, a trend towards shorter survival was observed in MM patients with DIS3 mutations (16). Other studies have shown DIS3 missense mutations in acute myeloid leukaemia, somatic deletions in breast cancer and loss of heterozygosity in superficial spreading melanoma (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%